The correlation between lifestyle health behaviors, coping style, and mental health during the COVID-19 pandemic among college students: Two rounds of a web-based study - Yi Zhang; Yi Zhang; Yi Zhang; Shuman Tao; Shuman Tao; Shuman Tao; Yang Qu; Yang Qu; Yang Qu; Xingyue Mou; Xingyue Mou; Xingyue Mou; et al. (Frontiers Media S.A., 2023)
BackgroundDuring the last months of 2019, worldwide attention has focused on a pandemic of COVID-19, and the pandemic spread rapidly, becoming a public health emergency of international concern. The Chinese government has quickly taken quarantine measures and the drastic measures incurred to curtail it, which could have harmful consequences for everyone's behavior and mental health.ObjectiveThis study aimed to investigate the correlation of influencing factors and mental health symptoms among Chinese college students according to two rounds of surveys during the COVID-19 pandemic.Materials and methodsThis study was divided into two stages of cross-sectional investigation. In February 2020 and May 2020, two cross-sectional surveys were conducted on college students in the above areas by means of cluster sampling. From February 4 to February 12, 2020, 14,789 college students completed the first round of online study from 16 cities and universities in 21 in China, excluding participants who completed the questionnaire, and finally included 11,787 college students. After 3 months, we also conducted a large-scale questionnaire survey based on the first study area to observe the behavioral changes and psychological symptoms of college students within 3 months. Using the convenience sampling method, a survey on the cognitive and psychological status of COVID-19 among college students was conducted in 21 universities in 16 regions in May 2020. The regions among the two surveys are divided into Wuhan (District 1), neighboring Hubei (District 2), first-tier cities, namely, Beijing, Shanghai and Guangzhou (District 3), and other provinces (District 4).Results(1) In the first survey, the average age of the participants was 20.51 ± 1.88 years. One-third of the college students were male. In total, 25.9 and 17.8% of college students reported depression and anxiety symptoms, respectively. College students, who reported higher ST, lower PA, higher soda beverage and tea beverage intake, have Chinese herbal medicine and vitamin drinking, and decreased frequency of diet had higher depression and anxiety symptoms. Moreover, infection risk, perceived resistance to COVID-19, concerns about physical symptoms, family/friends directly/indirectly contacted with confirmed cases, and seeking psychological counseling had significant associations with anxiety and depression symptoms. (2) In the second round of surveys, 6803 males (41.7%) and 9502 females (58.3%) had a mean age of 20.58 ± 1.81 years. The prevalence of depressive symptoms and anxiety symptoms during COVID-19 was 30.7 and 23.9%, respectively. (3) In both surveys, college students who reported having higher ST, lower PA, higher soda beverage and tea beverage intake, Chinese herbal medicine and vitamin drinking, and decreased frequency of diet also had higher depression and anxiety symptoms. Coping styles with COVID-19 partially mediate the association between some related lifestyle behaviors and anxiety and depression. The results of the conditional process model analysis support our hypothesis that lifestyle behaviors, and coping styles are both predictors of anxiety and depression symptoms, with both direct and indirect effects moderated by gender level. In logistic regression analysis, the correlation of depression and anxiety in the second rounds of the survey was higher than that in the first survey. In two surveys, there was a correlation between lifestyle health behaviors and coping style, gender and mental health.ConclusionsOur findings demonstrated that the prevalence of anxiety and depression in the two rounds of surveys was different, and the prevalence in the second round was higher than that in the first round, as well as that in the two rounds of surveys. All survey identified that unhealthy lifestyle behaviors were positively associated with depression and anxiety symptoms. Compared with the emerged city of risk areas, other pandemic regions have a lower risk of mental health problems. The survey findings complement each other. Lifestyle health behaviors and coping style alleviated mental health symptoms. COVID-19-related social stressors were positively associated with mental health symptoms. The study also suggests that at the beginning of the pandemic, the effective management of college students' mental health problems, corresponding coping measures and maintaining a good lifestyle play a key role in the prevention and control of other cities. Understanding the college students' lifestyle behaviors during COVID-19 lockdown will help public health authorities reshape future policies on their nutritional recommendations, in preparation for future pandemics.